SAQs as a Socio-Political Programme: Some Challenges and Opportunities - Ralph Levinson (Universidade de Lisboa, 2017)
In this article I argue for the role that approaches such as Socially Acute Questions (SAQs) can play in confronting the STEM discourse in the curriculum. For SAQs and similar approaches to be effective in enacting issues of social justice educators need to take account of local political contexts, the ethical and political assumptions which underpin values appertaining to social justice, such as concepts of communalism and libertarianism, and democratic practise in the school classroom where the students become co-enquirers in generating knowledge which aims to improve material realities. This is not a straightforward but one that demands reflection and critique throughout the process.